2023
DOI: 10.1021/acsaem.2c03370
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Cationic Interpenetrating Polymer Network Anion Exchange Membranes for Fuel Cells

Abstract: To facilitate large-scale commercial applications of anion exchange membrane fuel cells, high ionic conductivity and long-term durability of anion exchange membranes (AEMs) are crucial. Herein, poly(styrene-co-4-vinylbenzyl chloride) (PSVBC) without aryl ether linkages was synthesized by the radical bulk polymerization using styrene (St) and 4-vinylbenzyl chloride (VBC) as monomers. Then, using PSVBC as the framework material and secondary anion carrier, and polyquaternium-10 (PQ 10 ) as the main anion carrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…AFM images provided in Figure S5a–d demonstrated that the microphase separation of the prepared QP-1/x AEMs is uniform and distinct. The darker regions represent the hydrophilic parts, whereas the lighter regions are the hydrophobic regions [ 25 ]. A more significant and denser microphase separation is observed in the QP-1/2 AEM ( Figure S5c ), promoting rapid ion transport, and thereby increasing the hydroxide ion conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…AFM images provided in Figure S5a–d demonstrated that the microphase separation of the prepared QP-1/x AEMs is uniform and distinct. The darker regions represent the hydrophilic parts, whereas the lighter regions are the hydrophobic regions [ 25 ]. A more significant and denser microphase separation is observed in the QP-1/2 AEM ( Figure S5c ), promoting rapid ion transport, and thereby increasing the hydroxide ion conductivity.…”
Section: Resultsmentioning
confidence: 99%